A rare phenomenon of twin spotting: Phacomatosis pigmentokeratotica - Vaishali Wankhade; Vrutika Hasmukh Shah; Rajesh P Singh; Jayesh Mukhi (Wolters Kluwer Medknow Publications, 2019)
Phacomatosis pigmentokeratotica is a rare form of cutaneous mosaicism characterized by epidermal nevus usually nevus sebaceous, papular speckled lentiginous nevus, and extracutaneous anomalies. This type of twin-spot phenomenon (didymosis) is due to postzygotic crossing-over resulting in two homozygous daughter cells, representing the stem cells of the two distinct types of nevi and leading to additional extracutaneous defects. We report a case of this rare syndrome in a 4-year-old male child associated with skeletal anomalies.